Osteopathic education: A scoping review protocol. (March 2023) - MacMillan, A.; Draper-Rodi, Jerry
Abstract: Objective: The objective of this scoping review is to chart and appraise the available evidence regarding osteopathic education. Introduction: The extent and quality of the evidence regarding osteopathic education is not known. The available evidence mostly consists of small trials, qualitative interviews, cross-sectional surveys and conceptual commentaries, therefore a review to chart and appraise the available evidence is warranted. Inclusion criteria: The review is intended to include papers related to undergraduate, postgraduate and preregistration osteopathic education. Qualitative, quantitative, mixed methods and opinion pieces and grey literature will be sought. This review will exclude papers regarding education as a treatment modality and will exclude papers regarding osteopathy as a medical profession, as is seen in a North American context. Methods: The study will be conducted using OVID, PubMed, ERIC databases, and hand searches for key words will be conducted in key osteopathic journals. Reference lists of included papers will be screened for relevant papers, forwards and backwards citation tracking and key authors will be searched for similar publications which may be germane. Papers not available in English, French, Spanish, German or Portuguese will be excluded. There will be no limit placed upon date of publication. Implications for practice: This manuscript is the protocol for a systematic scoping review which is intended to answer the following questions: What is the extent and nature of the existing evidence regarding osteopathic education? Are there any elements of the literature which demonstrate good practice that can be adopted in wider osteopathic educational practice? Are there any gaps within the evidence base which subsequent research can explore? To date no systematic reviews have been conducted on this topic and this review will highlight the extent of the literature and guide future research priorities.